(4,6-Dibromo-m-phenylenedimethylidyne) tetraacetate - Guang-Liang Song; Shan Liu; Shui-Ping Deng; Yuan-Yuan Liu; Hong-Jun Zhu (Acta Crystallographica Section E, 2008)
The title molecule, C16H16Br2O8, lies on a crystallographic twofold axis. Weak intramolecular C—H...O hydrogen bonds may, in part, control the conformation of the molecule. In the crystal structure, molecules are connected into a two-dimensional network via weak intermolecular C—H...O hydrogen bonds.